Detection of Different Bovine Papillomavirus Types and Co‐infection in Bloodstream of Cattle. Issue 1 (3rd June 2014) - Santos, E. U. D.; Silva, M. A. R.; Pontes, N. E.; Coutinho, L. C. A.; Paiva, S. S. L.; Castro, R. S.; Freitas, A. C.
Summary: Bovine papillomavirus (BPV) is a diverse group of double‐stranded DNA oncogenic viruses. BPVs are classically described as epitheliotropic, however, they have been detected in body fluids, such as blood and semen. The presence of BPV in these sites can have implications for the dissemination of BPV. The aim of this study was to verify the prevalence of BPV types in cattle blood. A total of 57 blood samples were analyzed by PCR using BPV type‐specific primers to BPVs 1–6 and 8–10, and subsequent sequencing. Sequencing quality was determined using Staden package with Phred 20. Similarity analysis was performed with BioEdit and BLAST programs to assess the identity with known BPV types. Statistical analysis was performed by Fisher's exact test. The results showed seven different types of BPVs in the blood, with the exception of BPV 5 and 9. This is the first study that demonstrates BPVs 3, 6, 8 and 10 DNA in cattle blood. BPVs 1 and 2 were the viral types most frequent in blood, while BPVs 4 and 10 were the least frequent types. All the samples showed co‐infection by at least two BPV types. These data suggest that several BPV types may infect blood cells at the same time and demonstrate the possibility that the BPV infection in non‐epithelial tissue can occur without restriction to one or two viral types. These results can contribute to future studies aimed at the control and prevention of papillomaviruses.